Comparison of cell mechanical measurements provided by Atomic Force Microscopy (AFM) and Micropipette Aspiration (MPA). (July 2019) - Daza, Rafael; González-Bermúdez, Blanca; Cruces, Julia; De la Fuente, Mónica; Plaza, Gustavo R.; Arroyo-Hernández, María; Elices, Manuel; Pérez-Rigueiro, José; Guinea, Gustavo V.
Abstract: A comparative analysis of T-lymphocyte mechanical data obtained from Micropipette Aspiration (MPA) and Atomic Force Microscopy (AFM) is presented. Results obtained by fitting the experimental data to simple Hertz and Theret models led to non-Gaussian distributions and significantly different values of the elastic moduli obtained by both techniques. The use of more refined models, taking into account the finite size of cells (simplified double contact and Zhou models) reduces the differences in the values calculated for the elastic moduli. Several possible sources for the discrepancy between the techniques are considered. The analysis suggests that the local nature of AFM measurements compared with the more general character of MPA measurements probably contributed to the differences observed.